Operations Strategy Implementation in Perceptive Informatics - Mishra, Manoj (2010)
Until an organisation becomes successful there is no formal strategy formulation for the business. Businesses usually have a vision and try to map that with the market needs and in the process creating an organisation that becomes successful. With success comes growth and as more and more resources join the organisation comes the need for an organisation to stay focused and allow the resources to stay focus while achieving a common goal. As the organisation grows there is a need for capital to help organisation sustain the growth. Based on how the capital is acquired there is added responsibility on organisations to ensure they meet need of these shareholders while still ensuring market demands are met along-with internal resource demands. This leads into the organisations to become more formal and for higher management to focus strategically at the organisational activity. Academic world is a lot focused towards formulating strategy for a business and managing operations. But the overall function that delivers the product or service is not much talked about. This function is known by various names within various organisations, but its role stays the same. Few organisations call it as operations function. It is this function that helps organisation envisages strategy. Hence there is a need to understand how operations implements strategy. If implementation is poor, all other elements of strategic management become a waste of time and effort(Macmillan and Tampoe, 2000). As Macmillan et al. (2000) point out to implement strategy the firm needs appropriate capabilities, trained and motivated managers, strategic information and fluid and responsive systems and structures. This dissertation studies eClinical solution provider, Perceptive Informatics to understand how Perceptive implements its strategy. The study focuses on the key components that affect the overall operation i.e. Organisational Structure, Organisational Culture, Change Management and performance management. It became apparent in this dissertation that it is important for operations to have its own strategy and be aware of its internal suppliers and buyers. It helps plan strategy implementation and mitigates risk.